LSMS+ Program : Overview and Recommendations for Improving Individual-Disaggregated Data on Asset Ownership and Labor Outcomes - Hasanbasri, Ardina; Kilic, Talip; Koolwal, Gayatri; Moylan, Heather (World Bank, Washington, DC, 2021)
Established in 2016, the World Bank living standards measurement study - plus (LSMS+) program works to enhance the availability and quality of intra-household, self-reported, individual-disaggregated survey data collected in low- and middle-income countries on key dimensions of men’s and women’s economic opportunities and welfare. This report presents an overview of the LSMS+ program and provides operational guidance regarding individual-disaggregated data collection in large-scale household surveys, based on the experience with and analysis of the national surveys that have been implemented by the respective national statistical offices (NSOs) in Cambodia, Ethiopia, Malawi, Tanzania over the period 2016-2020, with support from the LSMS+ program.